Verificação de pilares mistos de aço e concreto submetidos à flexão composta reta: curvas de interação M-N - Fernandes, Matheus Oliveira (Universidade Federal de São Carlos, 2021)
Composite columns subjected to uniaxial bending moments are usually checked using normative recommendations, however, such checks do not include the use of high strength concretes. In this context, aiming to evaluate composite columns subject to eccentric compression and determine the pair of strength (normal force and bending moment), an analytical model based on strain compatibility was developed and implemented in the computational tool PM-MN (2021). With this tool it was possible to plot M-N interaction curves. Considering the uniaxial bending moments, expressions are defined that relate the values of normal force and moment resistance as a function of the neutral axis depth, geometry and strength of the components of the cross-section. The steel and concrete ultimate strains were defined based on the guidelines of ABNT NBR 6118 (2014). To validate the proposed model, two comparative analyzes were developed. In the first analysis, the M-N interaction curves from the PM-MN tool (2021) were compared to the models of ABNT NBR 8800 (2008), EN 1994-1-1 (2004) and ABNT NBR 16239 (2013). In the second analysis, values of normal force resistant to centered compression and moment resistance to pure bending were compared to literature results. The proposed model adequately estimated the eccentric compression strength when analyzing the cross section; the highest difference in relation to normative models was close to 6%. When analyzing the column, that is, taking into account the flexural buckling, the results of the interaction model implemented in the PM-MN (2021) were close to the results in the literature; the best estimate of strength showed an error close to 0,6%. Once validated, the tool was then used in a parametric study in which the influence of the following parameters was evaluated: cross-sectional shape, yielding strength of steel, compressive strength of concrete, bending axis and relative slenderness. The results showed that the effects of flexural buckling are less significant for the use of lower strengths of steel and concrete; on the other hand, the use of highest strengths increases the effects of flexural buckling, especially for slender columns.
Design of composite columns subjected to uniaxial bending moments: M-N interaction curves
Keywords: Pilar misto; Flexão composta reta; Eixo de flexão; Curva de interação M-N; Composite column; Uniaxial bending moments; Bending axis; M-N interaction curve; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS